PTH-307 Percutaneous management of pulmonary metastases arising from colorectal cancer; a systematic review. (22nd June 2015) - Lyons, N; Pathak, S; Daniels, I; Spiers, A; Smart, N
Abstract : Introduction: Radiofrequency ablation (RFA) has been successfully utilised in the management of colorectal hepatic metastases and has also been used in the context of colorectal pulmonary metastases (CRPM). The aim was to systematically review the evidence and to assess the safety and efficacy of ablative techniques in the management of CRPM. Method: A literature search was performed using PubMed, Embase, Cochrane Library, CINAHL and Google scholar databases to identify studies, which analysed ablative techniques and its efficacy in the management of CRPM. The primary outcomes of interest were overall survival and progression free survival. The secondary outcome measure was complication rates. Results: 7 studies were included in the review with a total of 553 patients and all of which used RFA for ablation. Mortality from ablation was <1% with overall survival ranging from 31–67 months. 1, 2 and 3 year survival ranges of 79–91%, 56–72% and 35–65% respectively. Local progression following ablation ranged from 9–22%. Major complication rates were noted in 1–8% of patients with minor complications ranging between 7–33%. 25% of patients required chest drain insertion post procedure. Conclusion: This is the first paper to systematically review the use of RFA specifically for CRPM. This review provides evidence that RFA is a safe and effective technique for the management of CRPM. However in the absence of large randomised controlled trials it is unclear where RFA should sit in the treatment algorithm for patients with pulmonary metastases from colorectal primaries. Disclosure of interest: None Declared.